ANALISIS PENERAPAN METODE MUROTTAL MAQAM KURDI DALAM MENGHAFAL AL QURAN JUZ 30 DI DTA MIFTAHUL FALAH DESA SINARTANJUNG KECAMATAN PATARUMAN KOTA BANJAR - riyanto, diki; Alamsyah, Aan; Nurdin, Agus; Abidin, Zaenal (TarbiyahMU, 2024)
The Koran is the holy book of Muslims, as well as the most important source of Islamic teachings which is a guide to life for its followers. It is appropriate for Muslims to always interact with the Koran, such as reading, memorizing and practicing its contents. In memorizing the Al-Quran, appropriate methods are needed to make it easier for students to memorize the Al-Quran, one of which is using the Kurdish Murottal Maqam Method. Kurdish Murottal Maqam is a method used to beautify the reading of the Koran without changing the rules in it. This research aims to determine the application of the Kurdish Murottal Maqam Method, as well as to determine the supporting and inhibiting factors for students in memorizing Al-Quran Juz 30 in Miftahul Falah DTA, Sinartanjung Village, Pataruman District, Banjar City. To identify the problems above, the research uses qualitative research methods with the type of field research (field research). Data collection was carried out through several stages, namely observation, interviews and documentation. Checking the validity of the data in this research used source triangulation and technical triangulation techniques. And data analysis in this research uses data analysis techniques from Miles, Huberman and Saldana 2014. The results of this research show that: 1) the process of implementing the Kurdish Murottal Maqam Method in Memorizing Al-Quran Juz 30 in the Miftahul Falah DTA is divided into 3 stages, including: Preparation Stage, Implementation Stage including: Semaan Activities, Question and Answer Activities. The final stage includes: Direct evaluation and indirect evaluation. 2) supporting and inhibiting factors in memorizing the Al Quran include: supporting factors include: Student motivation, teacher motivation, parents, methods, memorization targets, learning innovations, Murojaah in the classroom. The inhibiting factors include: Students, parents, there are the same verses.